enerapan Metode Weighted Product Untuk Penerima Insentif Karyawan - Romzi Rahman; Gunadi Widi Nurcahyo; Y Yuhandri (LPPM STIKOM Tunas Bangsa, 2024)
The development of science from time to time has succeeded in bringing humans into an era of information technology. Organizations need to change the way they manage and develop human resources in the face of technological change. Stakeholders need to evaluate employee performance periodically so that it can become a reference for determining employee incentives. Partial incentives will have a positive effect on psychological empowerment which will then also have a positive effect on employee performance. This research aims to build a Decision Support System in determining employee incentive recipients. The method used in this research is the weighted product method. This method has six stages, namely the alternative value of each criterion, the alternative value of each criterion after weighting, determining the preference weight of the criteria, calculating the preference value of Vector S, calculating the value of Vector V, and ranking results. The processed dataset comes from Institut Teknologi dan Bisnis Haji Agus Salim Bukittinggi. The dataset consists of 14 employee data with their respective criteria values. The results of this research can determine employee incentive recipients with an accuracy rate of 86%. Therefore, this research can be a reference for stakeholders to determine recipients of employee incentives in a certain period.